Evaluation of Crack Propagation During Cyclic Bending of Wire Strip - Biallas, Alina; Merklein, Marion (Proceedings of the 14th International Conference on the Technology of Plasticity - Current Trends in the Technology of Plasticity, 2024)
Steel fibers applied as concrete reinforcement like in Ultra High Performance Concrete reduce the wall thickness and thus the amount of concrete [1]. The process chain notch rolling and cyclic bending presents the foundation of an ecologically and economically efficient approach for production of steel wire fibers. For fundamental perception of the characteristics and interdependencies of the innovative production method, analysis by experimental model processes is required. Previous research determined influence of various process parameters on crack propagation [2], which is further analyzed in this study. As testing material, a DP600 sheet metal (t0 = 0.8 mm) is applied. Cyclic bending tests of wire strip with staggered amounts of cycles and varying bending angles are performed and evaluated based on load curves and micrographs. The analysis supplies identification of stages of crack propagation, which allows recommendations for process design regarding controllability and geometry of fracture. For supporting the analysis, stamping and cyclic bending is numerically implemented in the simulation software LS DYNA to picture the present strain stage applied during bending. The process evaluation together with the built simulation model can later be used as reference for a suitable numerical modeling of crack propagation that will enable a more flexible analysis of the process chain and parameter effects by simulation.<br
Created from Fastlane, Scopus look-up
Keywords: Bending; Damage; Crack propagation

Evaluation of Material Behavior for Wire Strip under Cyclic Bending Load and Preparation of an Experimental Test Method - Biallas, Alina; Merklein, Marion (Paper presented at ESAFORM 2021, 2021)
Steel fibers as concrete reinforcement improve the building material’s mechanical properties and enlarges its field of application. The production of steel fibers by the process chain notch rolling and cyclic bending promises energetic improvement compared to the conventional manufacturing process wire drawing. The innovative procedure is not yet researched extensively and modelling of the material behavior brings with it many challenges. Different stress states of both process steps require various material models and material failure must be considered. The study brings an appropriate modelling of the test sheet metal DP600 with a thickness of t0 = 0.8 mm for the second process step into focus. The wire strip’s notches are exposed to a cyclic tension-compression load for which high strength steel exhibits early yielding and a distinct transient region of the stress-strain curve after load reversal. For this reason, the isotropic-kinematic hardening model by Chaboche and Rousselier determined in tension-compression tests is validated by cyclic bending tests. For considering crack initiation, an appropriate ductile damage model for depicting material fatigue is identified. To allow practical realization of the process and validation of the material model, an experimental test method for manufacturing wire strip samples by notch stamping is introduc
Keywords: Kinematic hardening; Damage; Steel fibers

Fundamental Investigations to Evaluate the Influence of Notching Processes on a Subsequent Cyclic Bending Process for the Production of Wire Cores - Biallas, Alina; Ohmayer, Sophia; Merklein, Marion (Journal of Manufacturing and Materials Processing, 2023)
The production of wire cores by notch rolling and cyclic bending promises an ecologically and economically efficient manufacturing option for steel fibers. The paper at hand evaluates the influence of wire strips on cyclic bending by applying rolled wire strips of DP600 sheet metal (t0 = 0.8 mm) and a new cyclic bending testing tool. Analysis of material separation with varying parameters, rolling gap d and bending angle β, proves the interdependency of both process step, but indicates reduced adjustability of the notch rolling process. To enable better adjustability of the wire strip’s characteristics and analysis of their effects, wire strip production in the laboratory by notch stamping instead of rolling is aspired. The prior interaction analysis states the web height b, the notch angle α, and the hardening distribution as relevant wire strip’s characteristics to be replicated. Based on experimental analysis, an equivalent of notch rolling by notch stamping is deduced by considering the web height b identical for stamping and rolling, by adjusting the tool’s notch angle αt based on an equation considering geometric evaluations of α, and by taking advantage of the asymmetric hardening distribution of the outer notch which is comparable to rolled wire stri
Keywords: stamping; rolling; wire strip

Interaction analysis of a notching and cyclic bending process - Biallas, Alina; Merklein, Marion (Manufacturing Letters, 2022)
The economic and ecological efficient production of steel wire fibers for reinforcing concrete is essential for exploiting their potential to reduce the required amount of building material. An innovative production process bases on the process chain notch rolling and cyclic bending. A sheet metal is notched on both sides and subsequently bent under undulated motion for causing a cyclic bending load in the formed notches. Due to damage effects during the cyclic bending, cracks initiate. The damage procedure and crack growth is influenced by the previous notched sheet called wire strip and the characteristics of the bending process. To analyze these effects, an influence and interaction study of the notches on the cyclic bending process is aspired. Based on a two-staged experimental design, the notching parameters notch tip radius and web height, which correlate with the amount of strain hardening, as well as the bending parameter bending angle, for identifying the interdependency of both processes, are evaluated. For study execution, an experimental model test for applying a cyclic bending load on a notched specimen is introduced.
Keywords: Metal forming; Cyclic bending; Damage

Material Model for the Production of Steel Fibers by Notch Rolling and Fulling - Biallas, Alina; Merklein, Marion (Key Engineering Materials, 2021)
Concrete, which is reinforced by steel fibers, represents a multifunctional building material that is able to realize flexible but stable structures. As an alternative to the energy-intensive conventional production procedure wire drawing, a combination of a notch rolling and cyclic bending process is proposed by Stahl [1] to produce those fibers. Besides representing the properties of steel fibers and the overall process, the paper brings the layout of both process steps into focus. Since notch rolling for the production of wire strip is mainly unexplored, a general conceptual design of the process and the rolling tools is performed, supplemented by a similar study on the fulling process. To enable a further evaluation of the process chain and its relevant process parameters, a numerical and experimental test phase using strip of a dual phase steel DP600 with a sheet thickness of t0 = 0.8 mm is intended in future. For ensuring high-quality numerical model, relevant behavior of the test strip is characterized through appropriate experiments and according material models in the present pape
Keywords: Conceptual design; Rolling; Steel fibers